If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=2j-(-5)
We move all terms to the left:
7-(2j-(-5))=0
We calculate terms in parentheses: -(2j-(-5)), so:We get rid of parentheses
2j-(-5)
We add all the numbers together, and all the variables
2j+5
Back to the equation:
-(2j+5)
-2j-5+7=0
We add all the numbers together, and all the variables
-2j+2=0
We move all terms containing j to the left, all other terms to the right
-2j=-2
j=-2/-2
j=1
| 31=22+q/3 | | -108=9m | | -17+16x=16x-17 | | s/6-(-20)=26 | | 5+2x+1+x+16-7x=180 | | -54+22x=48-12x | | 3(m+8)=42 | | 3x2-4x-3=0 | | | | | | 18x+12=-12x+30x+24 | | t/4-7.2=-4.2 | | 3(m+8)=40 | | f/3-10=-8 | | 3x2+4x-1=0 | | 18+7x=24x+1 | | k/3+8=10 | | x/5+13=8 | | 5+x/2=34 | | 12x2-5x=2 | | 6(f+12)=96 | | x/5+15=5 | | 2/3+5/9x=3/4 | | .55p+6.99=11.9 | | --18-6k=6(1+3k) | | 9x+(6x+7)=5 | | 5x-12=8x-12+3x | | 11=w/3+7 | | 3a^2+15a-42=0 | | 2x^2-4x-960=0 | | 3/4k=8/12 | | 7(d+1)=98 |